Predicting Chinese Adolescent Internet Gaming Addiction From Peer Context and Normative Beliefs About Aggression: A 2-Year Longitudinal Study - Su, Ping; Yu, Chengfu; Zhang, Wei; Liu, Sha; Xu, Yang; Zhen, Shuangju (Frontiers in Psychology, 2018)
There has been growing concern over Internet gaming addiction (IGA) around the world. However, the risk factors and mediating mechanisms of IGA in Chinese youth remain largely unknown. A total of 323 Chinese adolescents (52.94% females, M age = 14.83, SD = 0.49, range = 13.50–16.50) completed questionnaires regarding peer victimization, deviant peer affiliation (DPA), normative beliefs about aggression (NBA), and IGA in the fall semester of 7th, 8th, and 9th grade. Structural equation modeling showed that 7th grade peer victimization predicted higher 8th grade DPA, which in turn was associated with enhanced 9th grade NBA, and ultimately, higher 9th grade IGA. In addition, 7th grade peer victimization made a unique contribution to 9th grade IGA through 9th grade NBA. The current study goes beyond previous research by using a 2-year longitudinal design and by taking into account both peer relations and individual cognitions as predictors of IGA. In addition, these findings have practical significance for improving intervention strategies targeting risk factors for adolescent IGA.